Cultural Representations in Border Literature: Reflecting on Harka Gurung’s Vignettes of Nepal - Gautam, Mani Bhadra (Bon Voyage, 2024)
This article explores the issues raised in Harka Gurung’s Vignettes of Nepal and analyzes them from historical perspectives. Cultural activities of the different geographical locations of Nepal that Gurung explores in the book are based on border, culture and the literature. Culture is a part of social practices interlinked to the cultural activities that connect people and literature of a society or a cultural community under a chain of social/socio-cultural activities. There might be different kinds of cultural groups within the same geographical border but they have the same kind of humanitarian values. However, they have some conflicting borders because of the space on performances and understanding of the cultural critics. Here, border refers to both the cultural community’s line as well as geographical territory. Many people respect to each-other’s culture but some of them disrespect borderland culture and literature that creates social disharmony in the name of cultural identity. Culture is a part of literary activities that helps to generate the literature and every literature is based on the culture. Gurung’s Vignettes of Nepal incorporates twenty essays based on different geographical borderlands, cultural practices and literature. He begins his essays from west of Kathmandu and concludes them coming to the east. In this study, this researcher selects particularly a few essays based on cultural borderland. Border, culture and literature are inseparable and so this study is on cultural cum ethno-geographical methodology as it studies the behavioral things of the people of different cultural communities. Objective of this paper is to show the connectivity of literature in the cultural borderland. To achieve the research goal, this study centers on historical places and observes cultural practices in Nepal. This researcher applies Mary Anderson and Dor Bahadur Bista’s ideas as supporting tools to the research in addition to Shalom H. Schwartz’s theory based on universal human values and cross-cultural psychologies. Finding of this paper is that the humanitarian cultures of the borders are key subjects to create the socio-cultural harmonies that help to generate the literature.